The Indigenous in Fernando María Guerrero’s Poems - Tiamson, Edgardo (Linguae et Litterae, 2010)
The American Thomasite María Morilla Norton tutored Fernando María Guerrero in English, the language of the then new conqueror of the Philippines. The academic interaction between student and mentor gave birth to an interesting article about the poet and patriot that appeared in the book Builders of a Nation (1914). She concluded her impressions with an affirmation that: It is a great deal to have read Fernando Guerrero but to know him is better, to have won his friendship is one of the best things the Philippines can give any foreigners, for he combines so much that is best in his race: its sensitive highbred feelings, noble intuitions and serious fidelity to the common task which, common though they may be, can ennoble a king or a poet. (Norton 1914, 211)